EMPIRICAL ANALYSIS OF PSYCHOLOGICAL HEALTH OF PRESCHOOL CHILDREN (Scientific journal of the Fergana State University, 2024)
In the article, the scientific research of scientists on the psychological health of 6-7-year-old children of preschool age, the research areas of Uzbek scientists focusing on the issue of human mental health, the impact of aggressive behavior on the mental health of preschool children, children living in rural and urban areas The article describes the practical analysis of aggressive behavior patterns, and the article also states that the level of aggressiveness of children of preschool age, that is, the students of preschool education organizations, is increasing in today's global world. mental health is damaged, it is natural for them to be more aggressive, as we mentioned above, there are many aspects of dependence on parents and educators. it is highlighted that even depending on his anger, his aggression may increase.